The Green Building Index (GBI) on landscape architecture scope of works - Nizarudin, Norhanis Diyana; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati (2011)
The Green Building Index (GBI) is a green rating system introduced by the Pertubuhan Arkitek Malaysia (PAM) to evaluate the performance of building across a broad range of environmental considerations. Apart from evaluating the building’s performance, the landscape design aspect has become a major part and parcel from the overall GBI assessment through the criteria of open spaces, landscaping and heat island effect. The paper is intend to highlight the review on the relationship of the GBI with the landscape architecture scope of works as well as the important roles played by the landscape architects from the Islamic point of view. It is hoped that this paper may possibly be an added knowledge about the GBI and the landscape architecture field and also as the key indicator towards enhancing the urban environment sustainability in the aspect of technology.